VAN DER POL-DUFFING OSCILLATOR WITH THE EFFECT OF HEREDITARY - Novikovа E. R. (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2017)
The paper presents a new mathematical model of the van der Pol oscillator, Duffing with external periodic influence given hereditarity. An algorithm for finding the numerical solution of the original model equation, which is based on the finite-difference scheme. A computer program implementing this algorithm. With this program built waveform and the phase trajectories for hereditarity oscillator Van der Pol-Duffing.